Virtual reality-based simulation learning on geriatric oral health care for nursing students: a pilot study - Lin, Pei-Chao; Wung, Shu-Fen; Lin, Pei-Chen; Lin, Yi-Ching; Lin, Cheng-Yu; Huang, Hsiao-Ling (BMC oral health, 2024)
There is a great need for training and education in the nursing curriculum to improve nurses' knowledge and skills to provide oral health care. A pilot study was conducted to evaluate the use of a virtual reality (VR)-based Oral Health Care Learning System to train geriatric oral health care among nursing students. Fifty undergraduate nursing students were randomly assigned to experimental (n = 25) and control (n = 25) groups. The experimental group received the VR-based simulation training on geriatric oral health care and the training was implemented twice at two weeks apart from March to November 2021. The control group did not receive the training intervention. Knowledge, attitude, and self-efficacy of geriatric oral health care as well as the intention to assist oral health care for older adults were assessed at the beginning, second, and fourth weeks. Generalized estimating equations were used to analyze the effectiveness of the VR-based simulation training. After the first round of training, students in the experimental group had significantly greater improvements in knowledge and self-efficacy of geriatric oral health care than in the control group. After the second round of training, students in the experimental group had significantly greater improvements in knowledge, attitude, and self-efficacy of geriatric oral health care as well as the intention to assist oral health care for older adult than in the control group. The VR-based simulation training was effective to improve undergraduate nursing students' knowledge, attitudes and self-efficacy of geriatric oral health as well as the intention to assist oral health care for older adults. The VR-based simulation learning system is an effective tool to provide practice experiences to build confidence and skills and to bridge the gap of understudied geriatric oral health content in entry-level nursing curricula. ClinicalTrials.gov (NCT05248542; registration date 21/02/2022).